Neutrophil-Lymphocyte-Ratio as Predictor of Morbidity and Mortality in Adults with Gastrointestinal Obstruction - Putranto, Agi S.; Pramesta, Bimo D (UI Scholars Hub, 2023)
Introduction. Gastrointestinal (GI) obstruction is a condition that often requires surgery and can lead to severe complications. The neutrophil-to-lymphocyte ratio (NLR) has been used as an inflammation indicator in various medical conditions, but research on the relationship between NLR and GI obstruction is still limited. Therefore, this study aims to evaluate the role of NLR as a cost-effective and simple preoperative predictor of postoperative mortality and morbidity, mainly surgical site infection, in adult patients with GI obstruction. Method. This cross-sectional study was conducted at Cipto Mangunkusumo General Hospital in Jakarta. The study sample consists of 150 adult patients with GI obstruction, with baseline characteristics including gender, age, type of GI obstruction, and neutrophil and lymphocyte levels. Results. Patients who died postoperatively had a higher average NLR (26.50) compared to those who survived (9.77). Multivariate analysis showed that NLR was an independent predictive factor for morbidity (OR = 1.37) and patient mortality (OR = 1.10). This study also identified the optimal preoperative NLR cut-off values as predictors of morbidity (9.95) and mortality (12.51) in postoperative GI obstruction patients, with high sensitivity and specificity. Conclusion. These findings indicate that NLR can be a reliable indicator for predicting surgical outcomes in patients with GI obstruction